Fixed points for multivalued mappings and the metric completeness - Sompong Dhompongsa (2018)
We consider the equivalence of the existence of fixed points of single-valued mappings and multivalued mappings for some classes of mappings by proving some equivalence theorems for the completeness of metric spaces.